Soil Bin Studies on Plug and Finger-type Onion Seedling Transplanting Mechanisms - Pandirwar, A. P.; Kumar, Adarsh; Mani, Indra; Gaikwad, B. B.; Sawant, C. P.; Bhoumik, Arpan (Journal of Agricultural Engineering, 2018)
A study was conducted to develop a plug- and finger-type onion seedling transplantingmechanisms in a soil bin and examine the effects of age of seedling and machine parameters(speed of operation, height of seedling drop, finger material) on plant spacing, plantingdepth, successful transplanting, furrow closure, filling efficiency and plant damage. Plantspacing ranged from 121.4 mm to 133.5 mm using plug metering mechanism, while itwas 167.9 mm to 195.0 mm with finger-type metering mechanism. The percent seedlingtransplanted and percent furrow closure with plug mechanism varied from 76.67 % to100 % and 73.33 % to 100 %, respectively; and in finger-type metering mechanism theyranged from 18.33 % to 78.33 % and 15 % to 73.33 %, respectively. Plug filling efficiencyranged from 96.67 % to 32.22 % with plug mechanism, and 95.28 % to 22.5 % with fingermetering mechanism. Percent seedling damage with plug mechanism ranged from 0 % to17.54 %, and was lower than 0 % to 31.05 % caused by finger-type metering mechanism.The performance of plug-type metering mechanism for onion seedling was closer to therecommended practices as compared to finger-type metering mechanism.